The role of social media in improving business communication among Muslim entrepreneurs in South Denpasar - Ramadiansyah, Sahri Aflah; Srikandi, Melati Budi; Prasetyo, Bambang Dwi; Khlil, Mazin Amir Mohammed (Islamic Communication Journal, 2024)
This study aims to explore the role of social media in enhancing business communication among Muslim entrepreneurs in South Denpasar. Using a qualitative approach, data were collected through in-depth interviews and observations of interactions on social media. This study identifies communication strategies implemented by Muslim entrepreneurs, challenges faced, and the impact of social media use on relationships with customers and business partners. Data analysis was conducted using a thematic analysis approach, which allows researchers to identify patterns and themes that emerge from the data collected. The results of the study indicate that social media has a significant role in strengthening business communication, facilitating better interactions, and supporting Islamic values ​​and principles in business practices. This study provides deeper insight into how Muslim entrepreneurs utilize social media and the ethical and social implications of such practices and recommends strategies to optimize the use of social media in business communication. Therefore, this study contributes to developing Islamic communication in business, where Islamic values ​​are integrated with business communication through social media. ***** Penelitian ini bertujuan untuk mengeksplorasi peran media sosial dalam meningkatkan komunikasi bisnis di kalangan pengusaha Muslim di Denpasar Selatan. Dengan menggunakan pendekatan kualitatif, data dikumpulkan melalui wawancara mendalam dan observasi interaksi di media sosial. Penelitian ini mengidentifikasi strategi komunikasi yang diterapkan oleh pengusaha Muslim, tantangan yang dihadapi, serta dampak penggunaan media sosial terhadap hubungan dengan pelanggan dan mitra bisnis. Analisis data dilakukan dengan pendekatan analisis tematik, yang memungkinkan peneliti untuk mengidentifikasi pola dan tema yang muncul dari data yang dikumpulkan. Hasil penelitian menunjukkan bahwa media sosial memiliki peran signifikan dalam memperkuat komunikasi bisnis, memfasilitasi interaksi yang lebih baik, dan mendukung nilai-nilai serta prinsip-prinsip Islam dalam praktik bisnis. Penelitian ini memberikan wawasan yang lebih mendalam tentang bagaimana pengusaha Muslim memanfaatkan media sosial dan implikasi etis serta sosial dari praktik tersebut, serta merekomendasikan strategi untuk mengoptimalkan penggunaan media sosial dalam komunikasi bisnis. Oleh karena itu, penelitian ini memberikan kontribusi terhadap pengembangan komunikasi Islam dalam ranah bisnis di mana nilai-nilai Islam diintegrasikan dengan komunikasi bisnis yang dilakukan melalui media sosial.